Characteristics of a Megajournal: A Bibliometric Case Study - Burns, C. Sean (Journal of Information Science Theory and Practice, 2015)
The term megajournal is used to describe publication platforms, like PLOS ONE, that claim to incorporate peer review processes and web technologies that allow fast review and publishing. These platforms also publish without the constraints of periodic issues and instead publish daily. We conducted a yearlong bibliometric profile of a sample of articles published in the first several months after the launch of PeerJ, a peer reviewed, open access publishing platform in the medical and biological sciences. The profile included a study of author characteristics, peer review characteristics, usage and social metrics, and a citation analysis. We found that about 43% of the articles are collaborated on by authors from different nations. Publication delay averaged 68 days, based on the median. Almost 74% of the articles were coauthored by males and females, but less than a third were first authored by females. Usage and social metrics tended to be high after publication but declined sharply over the course of a year. Citations increased as social metrics declined. Google Scholar and Scopus citation counts were highly correlated after the first year of data collection (Spearman rho = 0.86). An analysis of reference lists indicated that articles tended to include unique journal titles. The purpose of the study is not to generalize to other journals but to chart the origin of PeerJ in order to compare to future analyses of other megajournals, which may play increasingly substantial roles in science communication.